Functional Constipation and Dyssynergic Defecation in Children - Ilan J. N. Koppen; Marc A. Benninga (Frontiers Media S.A., 2022)
Defecation is a complex physiological process, which relies on intricate mechanisms involving the autonomic and somatic nervous system, the pelvic floor muscles, and the anal sphincter complex. Anorectal dysfunction may result in constipation, a bothersome defecation disorder that can severely affect daily lives of children and their families. In this review, we focus on different mechanisms underlying anorectal dysfunction and specific treatment options aimed at improving defecation dynamics in children with functional constipation.